2008
DOI: 10.1093/occmed/kqm142
|View full text |Cite
|
Sign up to set email alerts
|

Violence risks in nursing--results from the European 'NEXT' Study

Abstract: This study supports efforts aimed at improving teamwork-related factors as they are associated with a decrease in violence against nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
202
3
32

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 242 publications
(256 citation statements)
references
References 19 publications
19
202
3
32
Order By: Relevance
“…These findings differ from other studies (5,12,16,20) , which indicated increased exposure for professionals who work at night.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings differ from other studies (5,12,16,20) , which indicated increased exposure for professionals who work at night.…”
Section: Discussioncontrasting
confidence: 99%
“…Victims of violence at work in the past year had lower average age than those not exposed to violence in the last year, reinforcing findings of other studies (5,9,12,18,(20)(21) . This result can be explained from the perspective of young professionals who have less expertise in the development of their work activities and thus would have less ability to prevent attacks.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations